Satisfação e desempenho dos servidores técnicos administrativos de uma instituição federal de ensino superior - Santos, Carla Beatriz Soares dos (2013)
Brazilian public institutions are facing recovery actions to encourage a greater appreciation of its human resources through the development of new organizational policies. Even with all this development, there is still a lack of quantitative information updated, when available, present difficult concepts comparisons difficult. On the other hand, the relationship between job satisfaction and performance has attracted much attention throughout the history of industrial and organizational psychology. Many researchers believe that there is a causal relationship between satisfaction and performance, empirical studies, however, has not confirmed whether or not this relationship. This study aims to determine the impact of factors. The determinants of job satisfaction on the performance of individual server‟s administrative staff of a federal institution of higher education. The analysis was conducted through questionnaires server administrative staff of the Federal University of Santa Maria - UFSM in Santa Maria / RS, randomly, in its various sectors. The present study was carried out taking as basis the questionnaire developed by Valle (2007) and rotated with the method PLS Path Modeling (PLS-PM). The results of the study indicate the latent variable Challenging Work as primarily responsible for the performance perceived by the server. The low coefficient of determination suggests that the determinants of job satisfaction have little impact on the performance perceived by the Institution's servers. These results corroborate previous studies.